O processo de seleção do livro didático de ciências dos anos iniciais do ensino fundamental da rede pública Municipal de Ensino de Cascavel/Pr - Sgarioni, Prescila Daga Moreira (2017)
Accompanied by the curriculum, the textbook was established as one of the main instruments used in education institutions to approach and transpose the scientific knowledge acquired by humanity. It arises with the own school and is presente, in the course of history, in all societies. Even thought there are others teaching resources and technological advances, we understand the textbook as a precursor at the teacher and the student which measures the construction of knowledge and that is parto f the culture of many generations. Even with many transformations in society, the textbook still remains with relevant attribution in the teaching and learning process. In the Brazilian context, the public policies regarding textbooks count on the Textbook National Program - PNLD, responsible for the organization of the process of selection and distribution of textbooks to the students of the public educational institutions in the country. In doing so, with the objective of investigating which elements characterize the selection process of Science textbook for the municipal public school of Cascavel - PR. We opted for qualitative research in order to characterize the level of involvement of teachers, the guidelines and selection criteria of Science textbooks established by the responsible agencies. In the course of the study, three typs of scientific research were used: field research, bibliographical research and documentary research. The questionnaire was the data collection instrument used, applied to the teachers of the 5th grade of elementar school and to the pedagogical coordinators, responsible for organizing the selection process in municipal schools. We also used audio interviews recorded with the pedagogical coordinators responsible for organizing the selection process in Cascavel - PR. The data were organized in categories and subcategories were established based on content analysis, according to Bardin (2016), which allowed us to conclude that the process of selecting the textbook of Sciences for Elementary School, initial years in the municipality of Cascavel - PR, Occurred in a quick way, in a short period of time. This made the participation of teachers small, even though the municipality followed the guidelines passed by the Ministry of Education and have desired to involve all those the teaching and learning process.